2012
DOI: 10.1186/1742-2094-9-180
|View full text |Cite
|
Sign up to set email alerts
|

The persistent release of HMGB1 contributes to tactile hyperalgesia in a rodent model of neuropathic pain

Abstract: BackgroundHigh-mobility group box-1 protein (HMGB1) is a nuclear protein that regulates gene expression throughout the body. It can also become cytoplasmic and function as a neuromodulatory cytokine after tissue damage or injury. The manner in which HMGB1 influences the peripheral nervous system following nerve injury is unclear. The present study investigated the degree to which HMGB1 signaling contributes to the maintenance of neuropathic pain behavior in the rodent.ResultsRedistribution of HMGB1 from the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 48 publications
9
101
0
Order By: Relevance
“…Feldman et al used a tibial nerve injury (TNI) model to reveal the mechanism by which HMGB1 contributes to neuropathic pain (18). TNI induced redistribution of HMGB1 from the nucleus to cytoplasm of sensory neurons in rat DRG and cell lines, without changing total protein content, a finding that is consistent with the release mechanism of HMGB1 proposed in other cell types (19).…”
Section: Hmgb1 and Neuropathic Painsupporting
confidence: 61%
See 1 more Smart Citation
“…Feldman et al used a tibial nerve injury (TNI) model to reveal the mechanism by which HMGB1 contributes to neuropathic pain (18). TNI induced redistribution of HMGB1 from the nucleus to cytoplasm of sensory neurons in rat DRG and cell lines, without changing total protein content, a finding that is consistent with the release mechanism of HMGB1 proposed in other cell types (19).…”
Section: Hmgb1 and Neuropathic Painsupporting
confidence: 61%
“…Glycyrrhizin Tibial nerve injury Mechanical hyperalgesia (18) involved in pathophysiological rather than physiological pain. Shibasaki et al showed that HMGB1 was induced in the peripheral nerve in response to nerve injury and suggested that it contributed to the development of pain hypersensitivity, as revealed by antiHMGB1 anti body treatment in the neuropathic pain model (14).…”
Section: Hmgb1 and Neuropathic Painmentioning
confidence: 99%
“…There is evidence for involvement of exogenous and endogenous HMGB1 in pain processing (Chacur et al, 2001;Tong et al, 2010;Feldman et al, 2012). In particular, HMGB1 present in the DRG and spinal cord appears to participate in the pathogenesis of neuropathic pain (Shibasaki et al, 2010;Kuang et al, 2012;Ren et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Intrathecal administration of the neutralizing antibody against HMGB1 prevents or reverses the neuropathic pain/allodynia (Shibasaki et al, 2010;Ren et al, 2012) and bone cancer pain (Tong et al, 2010). Acute direct application of HMGB1 causes hyperexcitability of dissociated nociceptive DRG neurons isolated from rats (Feldman et al, 2012) and hypersensitivity of sciatic nerves to mechanical stimuli in rats (Chacur et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…76 The specific ASIC3 antagonist APETx2 77 inhibited Ca 2 þ influx, indicating a critical role of ASIC3 in sensory neuron excitation. Further, APETx2 was shown to reduce acid-induced inflammatory pain due to complete Freund's adjuvant 78 and slower the progression of osteoarthritis.…”
mentioning
confidence: 99%